Musculoskeletal Effects of Altered GH Action - Young, Jonathan A.; Zhu, Shouan; List, Edward O.; Duran-Ortiz, Silvana; Slama, Yosri; Berryman, Darlene E. (Frontiers in Physiology, 2022)
Growth hormone (GH) is a peptide hormone that can signal directly through its receptor or indirectly through insulin-like growth factor 1 (IGF-1) stimulation. GH draws its name from its anabolic effects on muscle and bone but also has distinct metabolic effects in multiple tissues. In addition to its metabolic and musculoskeletal effects, GH is closely associated with aging, with levels declining as individuals age but GH action negatively correlating with lifespan. GH’s effects have been studied in human conditions of GH alteration, such as acromegaly and Laron syndrome, and GH therapies have been suggested to combat aging-related musculoskeletal diseases, in part, because of the decline in GH levels with advanced age. While clinical data are inconclusive, animal models have been indispensable in understanding the underlying molecular mechanisms of GH action. This review will provide a brief overview of the musculoskeletal effects of GH, focusing on clinical and animal models.